Algeria : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper and Statistical Appendix deals with the issue of low growth in Algeria. A growth-accounting exercise indicates that negative total factor productivity growth explains Algeria's low growth rates. This paper highlights the sources of this low growth that mainly consist of incomplete structural reforms and the weaknesses of Algeria's institutions. It describes policy recommendations, focusing on the institutional reforms required to improve the business environment. The paper also analyzes Algeria's monetary policy in the context of volatile hydrocarbon revenues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet